Лев Данилович: «князь думен и хоробор на рати» чи «безчесний князь»? - Войтович, Л. (Україна в Центрально-Східній Європі, 2013)
У статті на підставі залучення низки нових джерел, в першу чергу латиномовних, здійснено спробу відтворення реалістичного портрета князя Лева Даниловича, пов’язаних з його життям і діяльністю, зокрема, тих, що стосуються його участі в європейькій політиці 1253– 1300 рр., взаємини з сусідніми володарями та рідними братами В статье на основе привлечения ряда новых источников, прежде всего латинских, предпринята попытка создать реалистический портрет князя Льва Даниловича, переоценено отдельные эпизоды его жизни и деятельности, в частности, относительно его участия в европейской политике 1253–1300 рр., взаимоотношений с соседними правителями и родными братьями. This study attempts to reproduce the real portrait of Prince Leo Danylovych, who was depicted in the first part of the Galicia-Volyn’ Chronicle as faithful comrade of his father, brave warrior and skilful commander, but in the second part of the Chronicle his image received negative traits of «dishonest prince». Historians only fragmentarily studied Leo’s image and never managed to resolve this contradiction. The author of the article involves some other sources, primarily Latin, previously unnoficed by scholars and on the basis of this new data evaluates episodes from the life of Prince Leo, including his role in European politics between 1253–1300 and his relationship with his neighbors and brothers.